Comparative Study of Imprint Cytology and Histopathology of Soft Tissue Tumors - Dutta, Sujit Kumar; Dasgupta, Senjuti; Bhattacharyya, Nirmal; Jain, Parul; Bose, Debdas; Biswas, Pranab Kumar (Indian Journal of Medical and Paediatric Oncology, 2017)
Background: Thecomponents of soft tissue are fibroblasts, collagen, vascular structures, fatty tissue, skeletal muscles, smooth muscles, and neural tissue. The real incidence of soft tissue tumors (STTs) is difficult to estimate because most of them are benign (Benign: Malignant-100:1). Aims: The aim of the present study was undertaken to note the patterns of presentation of patients with STTs and to evaluate the findings of imprint cytology (IC) and histopathological examination (HPE) of STTs. Materials and Methods: The present study was undertaken for 1 year. A total of 41 patients with clinically and radiologically diagnosed STTs were included in the study. Following surgery, imprint smear was taken for each tumor, before delivering the tissue to 10% formalin. HPE was subsequently performed. Results: The age of the patients ranged from 4 months to 80 years with a mean of 35.6 ± 17.5 years. The ratio of males to females was 1.05:1. HPE revealed that 21 (51.2%) tumors were benign and 20 (48.8%) malignant. Imprint smears revealed 16 (39%) tumors to be benign and 20 (48.8%) malignant. IC was inconclusive in 5 (12.2%) cases. The sensitivity of IC was found to be 89.5% and specificity 82.35%. The positive predictive value of IC was 85%. The accuracy of IC for diagnosis of both benign and malignant tumors was found to be 75%. Conclusion: IC of STTs is a rapid and simple method of intraoperative diagnosis, and it can serve as a viable alternative to frozen section biopsy, particularly in rural settings.
Keywords: Histopathology; imprint cytology; soft tissue tumors